5 - Decentralisation and Development: The Malawian Experience: DOI: 10.4314/ad.v29i2.22195 - Hussein , Mustafa K. (Africa Development, 2004)
The reorientation of the local government system towards decentralisation has been at the centre stage in most developing countries, including Malawi, since the advent of multiparty democracy in the 1990s. The justification for the adoption of some form of decentralisation is to promote democratic governance and participatory approaches in development. The primary purpose in this article is to analyse the context within which decentralisation initiatives are undertaken in Malawi and to assess the extent to which decentralisation promotes participatory approaches in development. This paper is based primarily on documentary research and supplemented by interviews conducted with senior officials from local authorities and with selected members of the public.